2014
DOI: 10.3390/molecules19068124
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Ferulate, a Component with Anti-Inflammatory Properties for Emulsion-Based Creams

Abstract: Ethyl ferulate (FAEE) has been widely studied due to its beneficial heath properties and, when incorporated in creams, shows a high sun protection capacity. Here we aimed to compare FAEE and its precursor, ferulic acid (FA), as free radical scavengers, inhibitors of oxidants produced by leukocytes and the alterations in rheological properties when incorporated in emulsion based creams. The cell-free antiradical capacity of FAEE was decreased compared to FA. However, FAEE was more effective regarding the scaven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…[14,15] For example, the esterification of FA has been employed to increase its effectiveness. [23] In the present study, we provide comparative evaluation of the antioxidant activities of FA and its amide and ester derivatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,15] For example, the esterification of FA has been employed to increase its effectiveness. [23] In the present study, we provide comparative evaluation of the antioxidant activities of FA and its amide and ester derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…[21,22] Further, several FA derivatives have been shown to be more lipophilic, thus increasing the ability of the derivatives to cross lipid-rich cell membranes and thereby offer better antioxidant potential. [23][24][25][26][27][28] In light of the aforementioned, we therefore studied structurally modified FA ester and amide derivatives and comparatively evaluated their in vitro antioxidant potentials as well as their possible protein binding interactions, using computational docking studies.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized this behavior may be responsible by simultaneous activity toward bacteria and pulmonary cells. Therefore, we evaluated the radical scavenging ability of 3 and 4 using DPPH (2,2-diphenyl-1-picrylhydrazyl) protocol [ 36 , 37 ]. Compounds 3 and 4 were evaluated at 1600, 800, 400, and 200 µM and exhibited all percentages of DPPH scavenging ability below 8% ( Figure 1 ), suggesting their low efficacy on radical processes.…”
Section: Resultsmentioning
confidence: 99%
“…There have been recent efforts to maximize the therapeutic value of FA by way of structural modification of FA to form FA derivatives in order to enhance physicochemical, antioxidant and therapeutic prospects. Recent investigations to maximize the therapeutic benefits of ferulic acid have demonstrated that structural modification could enhance physicochemical and antioxidant property of ferulic acid [7,8,17]. To prove the principle, we synthesized two new derivatives of ferulic acid and evaluated their protective effect against CCl 4 -induced liver injury in Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have implicated several FA derivatives for therapeutic potentials, such as anticancer [10 -12], antiatherogenic [13], and antibacterial agents [14], as well as anti-inflammatory activity [15,16]. Furthermore, the esterification of FA has also been widely used to increase its biological potency [17]. FA ethyl ester is derived by the addition of ethyl groups to FA by the esterification reaction between FA and ethanol [18].…”
Section: Introductionmentioning
confidence: 99%